Virus identification in tomato (Lycoperssicum sculentum L.) in five Departments of Guatemala. - Dardón, Danilo (2016)
A sampling was eonducted at the Departments of Zacapa, Jutiapa, Jalapa, Chimaltenango and Guatemala, to determine the presence of the tomato viruses causing the disease known as "Curly Top" and if they are transmitted by the "white fly" (Bemisia tahaci Gennadius), the presence of six virus: TMV, CMV, TEV, PVY, PVX and TSWV, and two geminivirus CdTV and SCLV was detected, The finding of a single TSWV positive sample makes it necessary to reconfirm its presence in Guatemala because it had not been reported before, Likewise, the geminivirus in tomato had not been reported in Guatemala, as well as the Chinesse Virus of Tomato (VCdT) and the Squash Curly Leaf Virus (SCL V), It was concluded that different viruses are associated to the "Curly Top" disease in tomato and that they cause a diversity of symptoms.